Measuring dynamic loads on a foldable city bicycle - Pirnat, Miha (Strojniški vestnik, 2011)
Strain gauges have been used to measure dynamic loads on a foldable bicycle while it is being ridden. Eight full, Wheatstone-bridge measuring points were used to measure the forces on the front and rear wheels, the handlebars, the seat and the pedals. These bridges were positioned at special measuring parts that simplified the measurements. Some of the measuring problems that were successfully resolved are described. The measuring took place on public roads where real-life data was gathered for various riding situations. For an easier interpretation of the data, a camera, an encoder and a GPS system were used. The results are shown for some riding situations and their impact on the design of foldable bicycles is discussed.
Keywords: dinamične obremenitve; dynamic loads; foldable bicycles; merilni lističi; strain gauges; Wheatstone bridge; Wheatstonov mostič; zložljiva kolesa